Inequality aversion, health inequalities, and health achievement - Wagstaff, Adam 1959-; Montenegro, Claudio 1958- (Policy research working paper, 2002)
This paper shows how value judgments can be explicitly recognized in measuring health ineqalities between the poor and the better-off, and how such inequalities can be included in assessments of countries' health indicators